2019
DOI: 10.3390/children6120134
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Caregiver Distress and Child Anxiety in Predicting Child Somatization in Youth with Functional Abdominal Pain Disorders

Abstract: Pediatric functional abdominal pain disorders (FAPD) are associated with adverse outcomes including increased somatization (e.g., heightened physiological sensations that include gastroenterological and non-gastroenterological symptoms) and increased functional disability. Caregiver distress and child anxiety are separately associated with the adverse outcomes of pediatric FAPD. However, the cumulative role of caregiver (i.e., stress, anxiety, and depression) and child psychological functioning (anxiety) in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…15,16 They also affect disability and other outcomes in children with functional abdominal pain. 17,18 Patients in our cohort exhibited somatization and catastrophizing consistent with previously described literature. We noted marked improvements in these variables with PENFS that were sustained at long-term follow-up.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…15,16 They also affect disability and other outcomes in children with functional abdominal pain. 17,18 Patients in our cohort exhibited somatization and catastrophizing consistent with previously described literature. We noted marked improvements in these variables with PENFS that were sustained at long-term follow-up.…”
Section: Discussionsupporting
confidence: 86%
“…1 Pain-associated impairment is prevalent in approximately one third of those affected, [2][3][4] and poor treatment outcomes are associated with significant psychosocial dysfunction. 5,6 The manifestations of chronic abdominal pain are associated with underlying visceral hyperalgesia, 7,8 disturbances in sleep, [9][10][11][12] and/or psychological comorbidities, [13][14][15][16][17][18] but the causeand-effect relationship is unknown. Visceral hyperalgesia is an altered sensation in response to non-noxious, physiological stimuli in the gastrointestinal (GI) tract and is often impacted by psychosocial factors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a meta-analysis including maternal mental disorders such as major depressive disorder and anxiety disorder; It has been determined that children have more physical health problems (5). Again, studies have shown that high stress level of caregivers predicts somatization symptoms in children (6). But in the majority of the studies investigating the psychological aspect in the etiology of functional constipation, children have been the main subject, and remarkably, there are very limited studies scrutinizing the mental state of parents, specifically in the age group where communication is expressed through body language (7).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a history of traumatic events and/or life stressors may lead to the development of persistent abdominal pain in a subset of youth [ 3 , 4 ]. A significant subset of youth with FAPDs also report a high rate of functional disability (e.g., minimizing physical activity) [ 5 , 6 ] and psychological impairment (e.g., anxiety, depression [ 5 , 7 , 8 ], somatic symptoms [ 9 , 10 ], and distress [ 11 ]) that may be related to the high rates of trauma experiences in this group [ 2 ]. Despite this, the link between pediatric FAPDs, trauma, and other clinical indicators, such as functional impairment and treatment response, have not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%